Improvement of the functional properties of pomegranate juice by ultraviolet, ultrasound treatment and probiotification - Alabdalı, Tareq Abdulrazzaq (My University, 2020)
This research aims to determine the combined usage possibilities of ultraviolet (UV) and ultrasonic (US) processes in the pasteurization of pomegranate juice and production of the functional pomegranate juice by fermented the final optimum point from pasteurization pomegranate juice with bacteria Lactobacillus plantarum. For this purpose, UV, US, and combined UV+US pasteurization of pomegranate juice were optimized using experimental designs, such as the central composite design and factorial design, and compared with the conventional pasteurization process. Total phenolic content, color a*, water-soluble dry matter (°Brix), turbidity, anthocyanin, DPPH, HPLC TPC, and yeast and mold count and were used as quality parameters during all of the processes. The results showed that the application of 50 °C, a 3.5 L/min flow rate, and 5.1 mW/cm2 UV dose, and 10 min US (200 Watt) reduced the microbial population below the detection limits. Lactobacillus plantarum was taken previously identified by genotypic characterization of the bacteria genomic DNA by PCR technique [1]. The Lactobacillus plantarum was added to pomegranate juice pasteurized by combined pasteurization. During four weeks’ storage at 5 °C, the enumeration of Lactobacillus plantarum and physicochemical and bioactive probiotic pomegranate juice properties were observed. Total phenolic content and antioxidant activity were greater in the fermented pomegranate juice than in unfermented juice after 24 h fermentation and for 28 days. The probiotic bacteria were valued after 24 hours of fermentation 9.64 log CFU/mL, in fermented juicy and viability of the probiotic bacteria remains over ∼7.11 log CFU/mL the length of the storage period for four weeks. No growth of yeasts and mold were observed in the fermented pomegranate beverage throughout preservation time.Incorporating UV + US processes into the pasteurization process can reduce microbial activity at lower temperatures and times than the conventional pasteurization process, thus preserving the bioactive compounds present in juices.

Araştırma, nar suyunun pastörizasyonundan elde edilen son optimum noktayı Lactobacillus plantarum bakterileri ile fermente ederek, nar suyunun pastörizasyonu ve fonksiyonel nar suyunun üretiminde ultraviyole (UV) ve ultrasonik (US) işlemlerinin kombine kullanım olanaklarını belirlemeyi amaçlamaktadır. Bu amaçla, nar suyunun UV, US ve kombine UV + US pastörizasyonu, merkezi kompozit tasarım ve faktöriyel tasarım gibi deneysel tasarımlar kullanılarak optimize edilmiş ve geleneksel pastörizasyon süreci ile karşılaştırılmıştır. Toplam fenolik içerik, renk a *, suda çözünebilen kuru madde (° Brix), bulanıklık, antosiyanin, DPPH, HPLC TPC ve maya ve küf sayımı tüm proseslerde kalite parametresi olarak kullanılmıştır. Sonuçlar 50 °C, 3.5 L / dak akış hızı ve 5.1 mW / cm2 UV dozu ve 10 dak US (200 Watt) uygulamasının mikrobiyal popülasyonu saptama limitlerinin altına düşürdüğünü gösterdi. Lactobacillus plantarum, daha önce PCR tekniği ile bakteri genomik DNA'sının genotipik karakterizasyonu ile tanımlanmıştı [1]. Lactobacillus plantarum, kombine pastörizasyonla pastörize edilen nar suyuna ilave edildi. 5 °C'de dört haftalık saklama sırasında, Lactobacillus plantarum sayımı ve fizikokimyasal ve biyoaktif probiyotik nar suyu özellikleri gözlendi. Toplam fenolik içerik ve antioksidan aktivite, fermente edilmiş nar suyunda, 24 saatlik fermantasyondan sonra ve 28 gün boyunca fermente edilmemiş meyve suyundan daha fazlaydı. Probiyotik bakteriler 24 saatlik fermentasyondan sonra 9,64 log CFU / mL, fermente sulu olarak değerlendirildi ve probiyotik bakterilerin canlılığı, dört hafta boyunca saklama süresi boyunca -7,11 log CFU / mL'nin üzerinde kaldı. Fermente edilmiş nar suyunda depolama süresi boyunca maya ve küf büyümesi gözlenmemiştir.UV + US işlemlerinin pastörizasyon işlemine dahil edilmesi, mikrobiyal aktiviteyi geleneksel pastörizasyon işleminden daha düşük sıcaklıklarda ve sürelerde azaltabilir, böylece meyve sularında bulunan biyoaktif bileşikleri koruyabilir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Ultraviolet irradiation; Ultrasound; Lactobacillus plantarum; Pomegranate juice; Functional beverage; Ultraviyole ışınlama; Nar suyu; Ultrason